Development of Organic Chemistry I Learning Module Integrated Experiment Based on Conceptual Change Model ED3U (Explore, Diagnose, Design, Discuss, Use) - Suryelita Suryelita; Zonalia Fitriza (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2018)
Organic Chemistry lecture requires the student to be able to think critically in getting knowledge and prove the facts through experiment. The problem of this lesson is the students have different ability to receive the concepts. To overcome this matter a teaching material, like a module which can facilitate the students who cannot follow lecture well is needed. Therefore, a module which is based on the conceptual change model ED3U (Explore, Diagnose, Design, Discuss, Use) was developed with the steps that activate critical thinking and skilled which appropriate for the learning outcome in alcohol lesson. The module was validated, tested for its practicality and affectivity to ensure the quality and functionality of the module to help students gained conceptual change. The instrument used for validity and practicality test was questionnaire, while test was used for evaluating its effectiveness. The Data was analysed using Cohen Momen Kappa Formula. The result showed that the module developed was valid, practical and effective and fit the category very high with the positive result for conceptual change.